Higher education spending - Kate Ogden; Madeline Thomas (Institute for Fiscal Studies (IFS), 2024)
How much does the Scottish Government spend on higher education, and what challenges does it face on university funding and living cost support?
Keywords: 330; Education and skills; Government finances and spending; Scottish Budget 2024-25; Student finance; Devolved government finances; Education; Higher education; Scotland